1989
DOI: 10.2135/cropsci1989.0011183x002900030002x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Stress on Grain Yield Response to Recurrent Selection in Maize

Abstract: Substantial yield reductions in maize (Zea mays L.) can be attributed to short‐duration drought in rainfed production areas. The objectives of this study were to investigate the effects of moisture stress in selection environments on response to mass and full‐sib recurrent selection and yield stability when selected materials were evaluated in environments with different levels of moisture stress. Five cycles of mass and full‐sib recurrent selection for grain yield were applied to population AS‐A under irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…It is concluded that the genetic expression differs under the two water regimens. This is consistent with results of other studies (Rebaut et al 1997;Li et al 2003) indicating that yield and drought tolerance are controlled by different sets of genes (Johnson and Geadelmann 1989;Atlin and Frey 1990;Li et al 2004). Differences in the additive and epistatic QTL between traits under water-stressed conditions indicate that the genetic expression also differs from trait to trait.…”
Section: Genetic Mechanism and Complexity Of Drought Tolerance Of Maisupporting
confidence: 92%
“…It is concluded that the genetic expression differs under the two water regimens. This is consistent with results of other studies (Rebaut et al 1997;Li et al 2003) indicating that yield and drought tolerance are controlled by different sets of genes (Johnson and Geadelmann 1989;Atlin and Frey 1990;Li et al 2004). Differences in the additive and epistatic QTL between traits under water-stressed conditions indicate that the genetic expression also differs from trait to trait.…”
Section: Genetic Mechanism and Complexity Of Drought Tolerance Of Maisupporting
confidence: 92%
“…Therefore, within the normal range of selection intensity, no line possessed the best combination of favorable genes for high yield in both irrigated and drought-stressed environments . These results agree with findings of many researchers (Ceccarelli, 1987 ;Ehdaie et al ., 1988 ;Ceccarelii,1989 ;Atlin & Frey 1989), yet they contrast with others (Frey, 1964 ;Roy & Murty, 1970 ;Quisenberry et al ., 1980 ;Johnson & Geadelmann, 1989 ;Whitehead & Allen, 1990) .…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have concluded that selection under favorable conditions produces lines suitable in both stress and nonstress environments (Frey, 1964 ;Roy & Murty, 1970 ;Laing & Fischer, 1979 ;Quisenberry et al ., 1980 ;Johnson & Geadelmann, 1989 ;Whitehead & Allen, 1990) . On the other hand, others have concluded that yield improvement under high-stress conditions requires selection strictly under those conditions (Arboleda-Rivera & Compton, 1974 ;Ceccarelli, 1987 ;Ceccarelli, 1989 ;Atlin & Frey, 1989) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that GE interactions are common under stress conditions, such as drought, cold, or pest attack, and make breeding progress difficult (Pswarayi and Vivek, 2008; Rodríguez et al, 2007; Butrón et al, 2008). A breeding program focusing on performance under stress can increase responsiveness of the selected populations (Johnson and Geadelmann, 1989; Bänziger et al, 2006). Therefore, a precise definition of the environmental and GE stress factors affecting yield should increase the opportunities for future improvements of grain yield.…”
mentioning
confidence: 99%